Uncertainty assessment of single-pass TanDEM-X DEMs in selected applications - Rossi, Cristian (Technical University of Munich, 2016)
SAR interferometry is a well-known technique for producing surface models. In the global scale, the quality of these models significantly increased with the use of bistatic systems such as the German TanDEM-X mission. Quality can be measured in two scales: a global and a local one. A global scale quality analysis involves measures for the complete scene, characterizing the whole correctness with a single parameter. A local scale investigates instead inside the single elevation model cell, discriminating the different quality obtained by the various terrains and media present in the scene. Objective of this research is to define strategies for assessing standard and alternative elevation accuracy methods and to inspect the different capabilities of the bistatic system. Four investigations are carried out for this purpose: agricultural fields (Lake Gala, Turkey), Mediterranean hills (Serra de Collcardus, Spain), subglacial volcanoes (Bardarbunga, Iceland) and cities (Berlin, Germany). Die SAR Interferometrie (InSAR) ist eine etablierte Methode, um topographische Modelle (Digital Elevation Models DEMs) der Erdoberfläche zu erzeugen. Durch die Nutzung neuartiger bistatischer SAR-Satellitensysteme wie TanDEM-X konnte die Qualität solcher globaler Modelle signifikant verbessert werden. Qualität ist dabei auf zwei verschiedenen Skalen messbar: einer globalen und einer lokalen. Eine Qualitätsanalyse auf globaler Skala beinhaltet Messungen an Aufnahmen großer Gebiete, welche die Korrektheit des ganzen Datensatzes mit einzelnen Parametern charakterisieren. Auf lokaler Ebene werden hingegen verschiede Qualitätsmaßzahlen für die unterschiedlichen Regionen, Materialien und Objekte innerhalb einer solchen Aufnahme unterschieden und individuell bewertet. Ziel dieser Arbeit ist es nun, Strategien zu definieren, um mit alternativen Methoden die Höhengenauigkeit einzuschätzen und die Fähigkeiten des bistatischen Systems TanDEM-X zur Lösung von Qualitätsproblemen zu demonstrieren. Untersuchungen an vier Gebieten werden zu diesem ...